Perspektif Mahasiswa: Peran Guru Sejarah dalam Membimbing Siswa SMA - Akmal Fairuz Syiraz; Ahmad Zulkarnaen; Febria Putri Rihandini; Hibban Muthiu Rahman; Nandang Budiman; Ibrahim Al Hakim (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study aims to analyze students' perspectives on the role of history teachers as learning facilitators through interactive methods such as discussions and history projects and motivators who use a storytelling approach to increase learning enthusiasm in learning history in high school. The focus of the research includes the history teacher's efforts in overcoming the notion of “History is Boring”, improving the quality of learning, and building students' interest in history. This research uses descriptive qualitative method with data collection techniques through interviews with History Education Study Program students. The implications of this research emphasize the importance of pedagogical innovation of history teachers in creating relevant, interactive, and value-based learning to form students' historical awareness.